6z=(0.5z-8)

Simple and best practice solution for 6z=(0.5z-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z=(0.5z-8) equation:


Simplifying
6z = (0.5z + -8)

Reorder the terms:
6z = (-8 + 0.5z)

Remove parenthesis around (-8 + 0.5z)
6z = -8 + 0.5z

Solving
6z = -8 + 0.5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-0.5z' to each side of the equation.
6z + -0.5z = -8 + 0.5z + -0.5z

Combine like terms: 6z + -0.5z = 5.5z
5.5z = -8 + 0.5z + -0.5z

Combine like terms: 0.5z + -0.5z = 0.0
5.5z = -8 + 0.0
5.5z = -8

Divide each side by '5.5'.
z = -1.454545455

Simplifying
z = -1.454545455

See similar equations:

| -96=2-7(2-4n) | | 4(2y+1)-7y=18 | | 84=6(1+3r)+6 | | 164=-8(1-5n)+3n | | log(12x)-log(2x)+log(3x)=log(8x)+log(9)+log(12) | | y=3e-25x+16e-32 | | 101=-8(X-3)-3x | | 34=x+x+(x-2) | | t/5-7=13 | | 5p-2q=23 | | 3(4s+4)=7 | | 4/3x3.14x343= | | 6(2l+2)=132 | | -1+3(7+3x)=83 | | 7m-3+2m=13+m | | sinx=1.5 | | 13x+5y=179 | | 25=40+3x | | 6(21+2)=132 | | 144=6(5x+4) | | 15x+7y=193 | | 3(a-2)=60 | | -88=2x-5(-2x+8) | | -4(8x-8)=192 | | (q-4)*7=-24 | | 3(x+1)+7=6(x+1)+63 | | 6+29=27+6+2 | | -92=7+3(4r-5) | | 550=(x-.05x) | | 10x+13y=11 | | -12+=16 | | 6(-7b-5)-5=-371 |

Equations solver categories